Life-cycle assessment of hybrid vernacular-modern technologies: a comparative study of the ecofordable house and conventional RC structures - Abdel Gelil Mohamed, Nermine (Frontiers in Built Environment, 2025)
This paper investigates the environmental benefits of adopting hybrid vernacular-modern building technologies through a detailed life-cycle assessment (LCA) of a residential prototype known as the “Ecofordable House” (EH). The EH integrates hybrid techniques, including partially reinforced interlocking compressed stabilized earth brick walls (ICSEB), jack arch and funicular shell roofing systems, and date palm midrib components. Its environmental impacts are compared to those of a reinforced concrete house (CH) use as the baseline conventionally adopted in the Middle East. The LCA follows a cradle-to-grave scenario, covering stages A1–A4, B1–B5, and C1–C4, with additional reference to stage D. The results showed that the CH has a value of 698.22 kg CO2e/m2, while the EH has a Global Warming Potential of 368.17 kg CO2e/m2, which represents a reduction of approximately 47% in global warming potential (GWP). Fossil-based emissions in the EH are 46% lower, biogenic emissions are reduced by 91%, and land use and land-use change (LULUC) have an impact reduction of 82%. The acidification potential is 43% lower, while eutrophication across freshwater, marine, and terrestrial resources is 28%–44% lower. The photochemical ozone creation potential (POCP) is reduced by 43%, and the resource depletion impact for elements and for fossil fuels is reduced by 50% and by 43%, respectively. Water use is 18% lower. Material production (A1–A3) is identified as the primary driver of environmental impacts for both prototypes. Fired clay bricks, concrete, and reinforcement steel are the major contributors toward GWP for CH, while Portland cement, concrete, and reinforcement steel dominate the GWP for EH, but with much lower values due to their reduced quantities. For CH, the major building part contributors are the foundation, roofs, and external walls, while in the EH, conventional reinforced concrete (RC) foundations and external walls are the major contributors. These results support the significant environmental benefits of adopting hybrid modern and vernacular building technologies and materials as ways of reducing environmental impacts while ensuring more durable and structurally sound buildings in hot, arid climates.